GIS as A Tool for Expansive Soil Detection at Sulaymaniyah City (Journal of Engineering, 2020)
Geotechnical engineering like any other engineering field has to develop and cope with new technologies. This article intends to investigate the spatial relationships between soil’s liquid limit (LL), plasticity index (PI) and Liquidity index (LI) for particular zones of Sulaymaniyah City. The main objective is to study the ability to produce digital soil maps for the study area and determine regions of high expansive soil. Inverse Distance Weighting (IDW) interpolation tool within the GIS (Geographic Information System) program was used to produce the maps. Data from 592 boreholes for LL and PI and 245 boreholes for LI were used for this study. Layers were allocated into three depth ranges (1 to 2, 2 to 4 and 4 to 6) m. A total of 1396 observations were used for producing the maps for both LL and PI, and 371 data for LI. Based on the results, the IDW method gives reasonable predictions depending on the results of R2 and RMSE. The results also showed that the study area has relatively large zones of high expansive soil that must be taken into considerations before performing any construction activity. These maps are essential for helping geotechnical engineers in making decisions and visualizing soils’ behaviors.